Antioxidant Activity of Zerumbone and Its Pharmacological Prospects in Oxidative Stress Conditions: A Narrative Review - Doloking, Haeria; Lallo, Subehan; Manggau, Marianti A; Rifai, Yusnita (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2023)
Introdiction: Oxidative stress is a condition caused by an imbalance between the level of oxidants in cells and tissues and the ability of the biological system to detoxify these reactive products. To compensate for the excess oxidant molecules, the human body requires the intake of antioxidant compounds through diet or medicinal plants to overcome the deficiency of these endogenous antioxidants. Zerumbone is the main bioactive compound of the Zingiber zerumbet L. Smith rhizome that was reported to have antioxidant activity and different pharmacological effects, like anti-inflammatory, anti-cancer, antidiabetic, immunomodulatory, anti-neurodegenerative disease, hepatoprotective, and gastroprotective. Aims: This review aims to gather available scientific research data regarding the antioxidant activity of zerumbone and its pharmacological prospects under conditions of oxidative stress. This paper is an overview of previous research on the various pharmacological activities of zerumbone and studies of its mechanism of action related to oxidative stress at the molecular level. The selected articles are related research reports for the 2010–2022 period, which can be accessed online through NCBI, Science Direct, MDPI, and Google Scholar. Result: The research results mentioned in this review paper can summarize knowledge to explain the pharmacological potential of zerumbone so that it can be used as a starting point or comparison in designing further research. Conclusion: The results of the reviews show that the various pharmacological prospects of zerumbone are related to oxidative stress conditions through various modes of action.